Metal resistance or tolerance? Acidophiles confront high metal loads via both abiotic and biotic mechanisms - Dopson, Mark; Ossandon, Francisco J.; Lövgren, Lars; Holmes, David S. (Frontiers in Microbiology, 2014)
All metals are toxic at high concentrations and consequently their intracellular concentrations must be regulated. Acidophilic microorganisms have an optimum growth pH < 3 and proliferate in natural and anthropogenic low pH environments. Some acidophiles are involved in the catalysis of sulfide mineral dissolution, resulting in high concentrations of metals in solution. Acidophiles are often described as highly metal resistant via mechanisms such as multiple and/or more efficient active resistance systems than are present in neutrophiles. However, this is not the case for all acidophiles and we contend that their growth in high metal concentrations is partially due to an intrinsic tolerance as a consequence of the environment in which they live. In this perspective, we highlight metal tolerance via complexation of free metals by sulfate ions and passive tolerance to metal influx via an internal positive cytoplasmic transmembrane potential. These tolerance mechanisms have been largely ignored in past studies of acidophile growth in the presence of metals and should be taken into account.